Socially Sustainable Work Processes in Danish Fringe Theatre: A Case Study of KULD - Rasmussen, Amalie Bjarnø (Peripeti, 2026)
Denne artikel undersøger det danske vækstlagsteater og dets position mellem amatør- og professionel scene. I artiklen fokuseres på ubetalt arbejde, kunstnerisk integritet og sociale bæredygtige praksisser. Artiklen identificerer alternative modeller for arbejdsprocesser og trivsel. This article explores Danish fringe theatre and its position between amateur and professional stages. It focuses on unpaid labour, artistic integrity, and socially sustainable practices. The study identifies alternative models for work processes and well-being.